THE ERGONOMIST AS A PROJECT TEAM MEMBER: PERCEPTIONS FROM THE PERSPECTIVE OF COMPETENCES AND TYPES OF KNOWLEDGE - Thais Elaine Vick; Marcelo Seido Nagano (Ação Ergonômica)
The article aims to call attention to the role of the ergonomist as an essential team member for product and system design to be used by people. The ergonomist is the professional who has the ability to conduct a project where science and application meet. The review of the literature is used to promote a discussion about the synergy between the ergonomist and the project team concerning two aspects: competences and knowledge typologies. This paper develops and characterizes four relationships between the role of the ergonomist and the work of a project team having the concepts of individual competences, collective competences and knowledge typologies. Some propositions of best practices are presented. The main conclusions highlight that the knowledge produced in the work, the technique and the model of man, as well as the competence to examine the real activity (future) are taken as the main attributes of the ergonomist that positively influence the work of project teams.